2011
DOI: 10.2174/092986711795328436
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nitric Oxide in Asthma in Adults: The End is the Beginning?

Abstract: Approximately 20 years after the initial report of the measurement of exhaled nitric oxide (NO) in the exhaled air of humans, numerous publications have evaluated the possible applications of the fraction of exhaled NO (FeNO) in patients with asthma. The aim of the present review is to evaluate the technical issues and confounding factors related to FeNO measurements, as well as the role of FeNO in the diagnosis of asthma, the evaluation of asthmatic patients and the guidance of treatment. Several other issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 96 publications
0
9
0
3
Order By: Relevance
“…Despite this limitation, FeNO can serve as an aid to a diagnosis, a measure of asthma control, and a predictor of steroid responsiveness. Also, there are confounding factors that affect FeNO measurements, including age, gender, atopy, and concurrent cigarette smoking . Clinicians should keep these in mind in FeNO measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, FeNO can serve as an aid to a diagnosis, a measure of asthma control, and a predictor of steroid responsiveness. Also, there are confounding factors that affect FeNO measurements, including age, gender, atopy, and concurrent cigarette smoking . Clinicians should keep these in mind in FeNO measurements.…”
Section: Discussionmentioning
confidence: 99%
“…34 Clinically, a significant decrease in FENO values beginning 2 to 6 weeks after initiation of ICSs is defined as a change of 20% for starting values of greater than 50 ppb and 10 ppb for values of less than 50 ppb. 30,35 If FENO values remain high despite corticosteroid treatment, levels of medication adherence need to be considered versus whether the underlying asthma represents a severe phenotype and unresponsiveness to usual treatment. Like eosinophil counts, increased FENO values predict a risk for an asthma exacerbation, [36][37][38] including exacerbations that might follow corticosteroid withdrawal.…”
Section: Fenomentioning
confidence: 99%
“…However, some caution is required in the interpretation of these results, although FeNO has been shown to be a diagnostic biomarker in patients with asthma, data in patients with COPD are less consistent, possibly due to the confounding influence of smoking. 47 49 The biomarker profiles of patients with asthma, COPD and overlapping asthma and COPD were assessed in a study by Iwamoto et al 50 The authors found that patients with overlapping asthma and COPD and COPD alone had a similar biomarker profile in plasma surfactant protein A, the soluble form of receptor for advanced glycation of end-products, and sputum myeloperoxidase levels, which differed from the profile in patients with asthma. In addition, elevated levels of sputum neutrophil gelatinase-associated lipocalin were observed in patients with overlapping asthma and COPD versus COPD alone, highlighting potential differences in the underlying mechanisms of these diseases and representing a finding that may warrant further study.…”
Section: Biomarkers In Identification and Managementmentioning
confidence: 99%